2021
DOI: 10.1007/s10433-021-00607-9
|View full text |Cite
|
Sign up to set email alerts
|

Is lifestyle change around retirement associated with better physical performance in older age?: insights from a longitudinal cohort

Abstract: A growing evidence base links individual lifestyle factors to physical performance in older age, but much less is known about their combined effects, or the impact of lifestyle change. In a group of 937 participants from the MRC National Survey of Health and Development, we examined their number of lifestyle risk factors at 53 and 60–64 years in relation to their physical performance at 60–64, and the change in number of risk factors between these ages in relation to change in physical performance. At both ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…People that changed their lifestyle by reducing risk factors for obesity, such as poor diet or inactivity, showed smaller physical declines over time in later life. This finding underlines the great potential for implementing healthy nutrition and exercise habits and thus increasing the disability-free life expectancy in the retirement phase [ 21 ].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…People that changed their lifestyle by reducing risk factors for obesity, such as poor diet or inactivity, showed smaller physical declines over time in later life. This finding underlines the great potential for implementing healthy nutrition and exercise habits and thus increasing the disability-free life expectancy in the retirement phase [ 21 ].…”
Section: Introductionmentioning
confidence: 93%
“…In most cases, this change is not gradual, but occurs abruptly one day when a person no longer needs to go to work and needs to start redesigning their everyday life [ 12 ]. A recent longitudinal study showed that 61% of people in this age group changed their lifestyle during the retirement phase [ 21 ]. People that changed their lifestyle by reducing risk factors for obesity, such as poor diet or inactivity, showed smaller physical declines over time in later life.…”
Section: Introductionmentioning
confidence: 99%